Journalism across cultures : an introduction - Obijiofor, Levi; Hanusch, Folker , 1975- (Palgrave Macmillan, 2011)
"In today's global digital world, journalists are required to be cognizant of ethical and cultural issues beyond usual national boundaries. Drawing on global examples, this text examines international journalism through the authors' wide variety of cultural, educational, teaching and learning backgrounds, including their professional and practical experiences. While existing books tend to be more focused on specific regions or specific aspects of journalism, this book addresses in a comprehensive way journalism across cultures from a truly global (and holistic) perspective. It analyzes media systems in Africa, Latin America, the Arab world and the Middle East, China, as well as North America and Western Europe. This text is truly interdisciplinary in theoretical and practical approaches because it draws on other fields such as media and cultural studies, anthropology, sociology, linguistics, as well as politics and international relations. It will provide an introduction to cross-cultural journalism and equip students with the skills and understanding they need today"-- Provided by publisher